ENGLISH-ISLAMIC PERSPECTIVE OF E-COMMERCE TRANSACTIONS: A SOLUTION TO CONTEMPORARY COMMERCIAL PROBLEMS - Anita Ali; Muhammad Ishfaq; Huma Ali (دی اسکالر)
E-commerce is a crucial aspect of the economy for firms that offer their goods or services online. E-commerce allows sellers or companies to target a wider audience than traditional retail. In the world of corporate technology, there has been tremendous expansion in recent decades. Technology is used by enterprises to gain a better position in the marketplace. The purpose of this research paper is to investigate Islamic viewpoints on e-commerce, notably in terms of transactions. It will also highlight the rights of the seller and customer according to Islamic law. The ethical perspective of E-Commerce in Islam will be investigated to explicit Muslims about how they might benefit from this new form of business. E-commerce contracts will also be analyzed in Islamic contract law that is crucial for business development and life improvement.  This paper will attempt to set out the paradigm for Islamic E-commerce, emphasizing the important success elements and ethics that will produce positive outcomes and provide a solution to the contemporary commercial problems.